PERSEPSI WISATAWAN ASING TERHADAP PELAYANAN KESEHATAN DI BALI: STUDI KASUS RUMAH SAKIT BALIMED - Putu Ayu Mira Maharani; I Nyoman Darma Putra; Syamsul Alam Paturusi (Magister Tourism Study, Faculty of Tourism, Udayana University, 2018)
Foreign tourists realize that health is as important as the need to travel, therefore travel health should be one important factor in supporting tourism in Bali. This study aimed to analyze the perception of foreign tourists to the performance of health services in BaliMe?d Denpasar Hospital in terms of ve categories of services that cover all aspects of the form of direct, reliability, responsiveness, assurance, and empathy, as well as to determine the service indicator most dominant in uencing tourist satisfaction over the performance of health services provided. Data were collected by distributing questionnaires and interviews to the foreign tourist who came for treatment or hospitalization at the BaliMe?d. The result of the study shows that the perception of tourists to medical services is in the category of satisfactory and should be maintained, while the relationship between indicators of health services in this hospital in terms of the expectation value of foreign tourists to the perception of health services is very strong.